Do disabled people need a stronger social model: a social model of human rights?. Issue 7 (14th September 2019) - Berghs, Maria; Atkin, Karl; Hatton, Chris; Thomas, Carol
Abstract: We introduce the social model of disability by reflecting on its origins and legacy, with particular reference to the work of the Union of the Physically Impaired against Segregation. We argue that there has been a gradual rolling back of the rights and entitlements associated with the social model of disability. Yet no alternative for the social model has been proposed in response to such threats to disabled people's human rights. Disabled people need a stronger social model that acts as a means to a society which enables and ensures their rights; the right to live a dignified life, as well as to live in an environment that enables people to flourish with disability.